Um anarquista que amava o direito: o pluralismo normativo de Robert Cover - Flores, Maurício Pedroso (Universidade do Vale do Rio dos Sinos, 2018)
The American jurist Robert Cover developed important reflections on fundamental aspects of the theory of law, such as the genesis of social normativity and the legitimacy of the courts. Since he could not systematize his writings in a relatively coherent way, Cover’s work stood as a source of many reflections, but also many questions, for his commentators and critics. The different interpretations and appropriations of his thought show that his thinking is still largely an open book. The aim of this thesis is to present Cover’s main ideas and to demonstrate that his thinking remains current and relevant as a source of insights into contemporary law. To do so, our exposition takes up two tasks. First, it seeks to reconstruct Cover's thinking from his main texts and ideas. In a second moment, it proposes a speculation on possible theoretical paths pointed by his work. Our reconstruction of is centered on two major milestones of his work: the essays Nomos and Narrative (1983) – where Cover elaborates his most influential concepts, like nomos and jurisgenesis – and Violence and the Word (1986) – in which Cover suggests that legal interpretation is established in a "field of pain and death" and is inseparable from violence. The central messages of these two essays have been interpreted by commentators and critics as partially or totally contrary. Considering them as equally fundamental to understanding Cover's thinking, the paper resorts to some of these debates in search of an interpretation that can reconcile the two approaches. Finally, based on this interpretation, it suggests that Cover's work could be read as containing the idea of a normative pluralism, an expression that has two meanings here: it connotates not only the adoption of a plurality of normative sources but also the presence of normative criteria to evaluate law critically.
Keywords: Robert Cover; Pluralismo normativo; Nomos; Jurisgenesis; Violência; Robert Cover; Normative pluralism; Nomos; Jurisgenesis; Violence; ACCNPQ::Ciências Sociais Aplicadas::Direito